Power quality management for grid-connected microgrid - Wang, Yizhu (Nanyang Technological University, 2023)
Distributed generation technology has been rapidly developed to enable large-scale development and utilization of renewable energy sources, since the global energy crisis as well as the environmental degradation has become more and more serious today. Microgrid is an effective way to coordinate the conflicts between distributed generation and the main power grid, ultimately improving the efficiency of distributed generation supply, and it has become a hot topic of research.